ADAPTASI PERILAKU PETANI PADI DAERAH PINGGIRAN KOTA DI ERA COVID-19 SERTA PENGARUHNYA TERHADAP USAHATANI (Studi Kasus: Desa Sukabakti, Kecamatan Tambelang, Kabupaten Bekasi) - Yomitha Faradina; Yayat Sukayat (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Covid-19 has an impact on the agricultural sector and farmers so that it affects their cultivation, marketing and income processes, thereby changing farmers’ behaviour to survive and maintain the availability of staple food. The purpose of this study is to find out the characteristics of rice farmers and analyse the adaptation of suburban farmers’ behaviour and their influence on farming during the Covid-19 pandemic. This research is using qualitative research with a case study approach at Sukabakti Village, Bekasi Regency. The sample selection using snowball sampling method. The results of study showed that the Covid-19 pandemic has an influence on rice farmers in the suburbs of Bekasi and Jakarta. In rice farming farmers have a considerable influence on grain sales, labor and distribution of fertilizer subsidies, caused by the lack of knowledge of farmers in marketing grain so that farmers are difficult and often suffer losses due to grain that is valued quite low. Based on this influence, farmers make several adaptations so that they can to survive during Covid-19. Adaptations are reduction of labor into family labor, reduction of sales on rice grain, doing side work as traders,  reduction of fertilizer dose, receiving government support.